The Application of Student Worksheets Based on PhET Simulation to Increase the Concept Understanding in Hooke's Law - Sudirman Sudirman; Muhammad Qaddafi (Universitas Muhammadiyah Makassar, 2023)
This study aims to find out: 1) the overview of students ' concept understanding before being taught by using student worksheets based on PhET simulation, 2) the overview of students' conceptual understanding after being taught using student worksheets based on PhET simulation, 3) the increase of conceptual understanding before and after being taught using students’ worksheet based on PhET simulation. This pre-experimental study was carried out with one group pretest-posttest design. The subjects of this study were all of the students of class XI MIA 2 Madrasah Aliyah Lita, Bone Regency. The sampling technique used was purposive sampling. The instruments used was a test to measure understanding of the concepts learned. The results of the descriptive analysis show that the average scores of understanding concepts before using the student worksheet based on PhET simulation is 28.10, while the average value after being taught using the students worksheet based on PhET simulation is 75.71. It indicates that there is an improvement in students’ concept understanding before and after using the student worksheet based on PhET simulation. Meanwhile, the t-count obtained is 5.43 and the t-table obtained is 2.08. Thus, there is a significant difference between the understanding of the physics concept of class XI MIA 2 Madrasah Aliyah Lita Bone regency before and after applying PhET-based worksheets simulation.